A model for rock dissipated energy estimation based on acoustic emission measurements - Zhang, Penghai; Guan, Kai; Deng, Wenxue; Liu, Xige; Qin, Tao; Ma, Qingshan (Frontiers in Earth Science, 2023)
The temporal domain of dissipated energy during rock damage and failure is commonly quantified using loading and unloading tests or elastic mechanics-based theoretical calculation methods. However, these approaches cannot be applied to obtain the spatial distribution of rock dissipated energy. This paper presents a novel model to estimate rock dissipated energy based on acoustic emission measurements. The proposed model is used to estimate the temporal and spatial distribution of dissipated energy in a sandstone specimen under uniaxial compression conditions. The results indicate that the model well describes the energy dissipation evolution trend in the temporal domain with an error of 38.63% compared with results calculated using the traditional method. The dissipated energy concentration area estimated by the model is located near the macroscopic fractures, which indicates that the model can describe the evolution process of rock energy dissipation in the spatial domain.